Diseño de un sistema de control semiautomático capaz de realizar el roscado en envases PVC empleados en la exploración sísmica. (2023)
For the development of this project, an analysis of operational parameters within the company JACARI Ltda. for the threading process in PVC containers used in seismic exploration is carried out. Based on this, a semi-automatic system for the threading of containers is designed and implemented, with the purpose of having a constant production within the plant, considering that the threading of PVC pipes is the most strenuous and tedious process within the production line.